Anemia in celiac disease is multifactorial in etiology: A prospective study from India. Issue 5 (2nd August 2018) - Berry, Neha; Basha, Jahangeer; Varma, Neelam; Varma, Subhash; Prasad, Kaushal Kishor; Vaiphei, Kim; Dhaka, Narendra; Sinha, Saroj K; Kochhar, Rakesh
Abstract : Background and Aims: Anemia is one of the most common extraintestinal manifestations of celiac disease (CD), with iron deficiency anemia (IDA) being the predominant cause. However, anemia in CD can have varied etiologies, including mixed nutritional deficiency. We aimed to study the prevalence and etiology of anemia in CD in a north Indian population. Methods: In this prospective observational study, consecutive patients with documented CD between January 2012 and December 2013 were included, and all patients underwent detailed clinical assessment; hematological investigations including iron profile, serum folate, and vitamin B12 levels; and esophageoduodenoscopy with duodenal biopsies for histopathological examination. Prevalence of anemia and different deficiencies were calculated, and a correlation between hematological parameters and histological findings was found. Results: Of the 103 patients studied, anemia was detected in 96 patients, giving a prevalence of 93.2% with a baseline hemoglobin of 8.94 ± 2.54 g/dL. Overall, iron deficiency was seen in 84 (81.5%) patients, followed by vitamin B12 deficiency in 14 (13.6%) and folate deficiency in 11 (10.7%) patients; 17 (16.5%) patients had anemia due to mixed nutritional deficiencies, and 4 (3.9%) patients had anemia of chronic disease. The mean hemoglobin and median ferritin levels were significantly lower in patients with severe villous atrophy compared to those with mild atrophy. Conclusion: Anemia in patients with CD is multifactorial. Even though iron deficiency is the most common cause, other nutrient deficiencies should always be explored. Abstract : Anemia in celiac disease is multifactorial in etiology, with iron deficiency anemia being the most common etiology. Other etiologies include vitamin B12 deficiency, folate deficiency, anemia due to mixed nutritional deficiencies, and anemia of chronic disease.